Indonesia Menuju Parlemen Bikameral - Haniah Hanafie (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2004)
This article elaborates on the bicameral parliamentary system in Indonesia, which is a new step, considering that until now the Indonesian Parliament adhered to a Unicameral (single-chamber) system, namely the DPR (People’s Consultative Assembly). Whereas now (as a result of the 2004 Elections), it has produced members of the People’s Representative Council (DPR) and the Regional Representative Council (DPD) which will later become two chambers.